M&A short-term stock abnormal return analysis: empirical evidence from US large M&A transactions 2002-2005 - Xia, Yuan (2010)
In this paper, I make the analysis by using the event study method. I choose the 5days event period and calculate the abnormal return of the bidders’ stock price for my sample merger and acquisition transactions during a period from 2002 to 2005. After analysis of the cumulative abnormal return for each of the groups under different classification basis, I try to get some conclusion about the short-term bidders’ stock performance and also get some implications from the analysis. I also make the regression analysis and statistical test so that to find out the determinate factors which significant effect on the movements of bidders’ stock price during the event window. My predicted result in the paper is that the stocks for the bidders perform better and get positive abnormal return when the merger and acquisition transactions are finished by cash payment method rather than the stock payment method. However, more transactions are paid by both stock and cash method together and combined other methods. The stock abnormal return is also affected by the relative size between target and bidder. For the multiple bids during the sample period, the market reacts more active and positive to the first bids than the later bids.